Towards zero carbon emission at YTU Davutpasa Campus - Sukur, Fatma Zehra; Ozkaya, Bestami; Yilmaz, Tamer (INDERSCIENCE ENTERPRISES LTD, 2024)
Yildiz Technical University has developed a sustainable campus model by investing in renewable energy sources, implementing a zero-waste management system, and installing water-efficient irrigation systems. The Davutpasa Campus has recently become a hub for training, research centres and other R&D activities to improve sustainability. It succeeded to decrease its total energy consumption by 15% and transportation actions by 7% in comparison to the reference year 2018. The reduction of emissions was greatly achieved by carbon offsets, which resulted in a 50% decrease as compared to 2018. This strong commitment to sustainability has observed YTU's rise in green university rankings.
Keywords: sustainability; green universities; emission sinks; carbon offsetting; END-USE; Environmental Sciences & Ecology